Socialtechnological Man. - Gonzalez, Nancie L. (Oxford : Taylor & Francis Group, 2020)
This volume presents studies of societies ranging from ancient Peru to contemporary Israel that are concerned with human activity in arid environments. It discusses the rise and fall of water management system and reviews its broader physical, social, and technological setting.
7 Drought versus Desertification: The Case of the Sahel -- 8 Some Observations on Adaptation to Semi-arid Environments.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Droughts-Social aspects; Electronic books